Criminal Offence of Falsifying Authentic Deed In The Implementation of Notary Department - Ici Kurniasih (Authentica, 2020)
The notary in conducting his profession is not infrequently called by the police law as a suspect in connection with the forgery of the authentic deed he made, that the notary can be used as a suspect if the notary Deliberately make a false deed as requested by the parties, when the notary knows that the parties do not meet the terms of the validity of the alliance. This indicates that the notary does not cling to the notary Act (UUJN) and the notary Public Code of ethics, which resulted in a notary criminal can perform authentic acts of fraud/deed. The Notary Law (UUJN) does not formulate the application of the sanctioned sanctions but a legal action against violations committed by the notary would contain counterfeit elements of deliberate intent/omission in the creation of Authentic letter/deed whose information is false can be qualified as a criminal offence committed by the notary who describes the evidence of involvement deliberately commit the crime of counterfeit authentic deed. The research is a normative juridical study. Normative research examines and analyzes the legal norms that have been established by the competent authorities for that, so the type of research used in this research is prescriptive, namely the process to find the rules Legal, legal principles, and legal doctrines to address the issues faced. The results of this research show that the legal consequences for the notary criminal who commit the crime of authentic deed are: in terms of criminal law, the notary threatened to be sentenced to the threat of article 264 Criminal Code about the counterfeiting of authentic deed with the threat Maximum sentence of eight years in jail. In terms of civil law, notaries can be sued for damages by the parties who feel harmed. In addition, the relevant notary public may be subject to administrative sanctions from a notary Organization (THIS) in the form of: Oral strikes, written strikes, temporary dismissal, dismissal termination, disrespectful termination.Keywords: criminal acts of counterfeiting, authentic deeds, notary sanctions